KEPRAKTISAN PENGEMBANGAN PERANGKAT PEMBELAJARAN SIMULATOR BAGIAN MESIN UNTUK MENINGKATKAN KETERAMPILAN KADET DALAM PENGOPERASIAN MESIN KAPAL NIAGA - Saransi, Faisal; Wahid, Abdul; Kamal, Kamal (Fakultas Teknik Universitas Islam Makassar, 2024)
This study aims to: 1) obtain an overview of the need for the Development of Machine Parts Simulator Learning Devices to Improve the Skills of Cadets in Operating Commercial Ship Engines in universities; 2) obtain comprehensive information in designing the Development of Machine Parts Simulator Learning Devices to Improve the Skills of Cadets in Operating Commercial Ship Engines; 3) produce the Development of Machine Part Simulator Learning Devices to Improve the Skills of Cadets in Operating Commercial Ships Engines that are valid based on the assessment of the validators; 4) produce the Development of Machine Parts Simulator Learning Devices to Improve the Skills of Cadets in the Practical Operation of Trading Vessel Engines; 5) resulted in the Development of Machine Parts Simulator Learning Devices to Improve the Skills of Cadets in the Effective Operation of Trading Vessel Engines. The subjects of this study were students and lecturers of the Makassar PIP Engineering Study Program. The research and development procedure used is the ADDIE model: (1) Analysis, (2) Design, (3) Development or Production, (4) Implementation, and (5) Evaluation. Data collection techniques used are observation, interviews, tests, questionnaires and documentation. The research instrument used an instrument for observing the implementation of learning, a test instrument for assessing student learning outcomes, and a validation sheet for learning tools. The data analysis technique is carried out by (1) analyzing the level of validity, (2) analyzing the level of practicality, and (4) analyzing the response data of students and lecturers. The results of this study indicate that it is necessary to develop a machine part simulator learning device to improve the skills of cadets in operating commercial vessels. The results of the validation test showed that the learning tools and several research questionnaires were declared to be very valid based on the assessment of the experts. Furthermore, the results of the practicality test also stated that this device was proven to be very practical based on the results of observations of the implementation of learning and questionnaire responses from lecturers and students.